Pengaruh Faktor Sosial Ekonomi terhadap Efisiensi Input Produksi Kelapa Sawit Rakyat - Kurniati, Sri Ayu; Tibrani (JURNAL AGRICA, 2026)
The palm oil industry is closely linked to the Sustainable Development Goals (SDGs), particularly through its contribution to improving community welfare. Rokan Hulu Regency in Riau Province is one of the regions with the highest palm oil production; however, productivity remains relatively low, especially among smallholder plantations. The mismatch between the natural potential of plantations and farmers’ capacity to utilize production inputs, coupled with high production costs and low-income levels, has pushed many farmers into extreme poverty. This study aims to examine the level of technical efficiency and the influence of socioeconomic factors on the efficiency of input utilization in smallholder oil palm farming. Primary data were collected from 160 smallholder oil palm farmers in the Rokan IV Koto and Ujung Batu Districts. Data Envelopment Analysis (DEA) was employed to estimate technical efficiency, while a Tobit regression model was used to analyze the socioeconomic factors affecting efficiency. The results indicate that smallholder farmers are inefficient in utilizing production inputs. In particular, the allocation of seeds and labor, as key economic inputs, requires greater attention and prioritization. The Variable Returns to Scale (VRS) efficiency score is higher than the Constant Returns to Scale (CRS) score, indicating that smallholder oil palm farming operates under conditions of increasing returns to scale. Socioeconomic factors that significantly influence technical efficiency include age, education level, membership in farmer groups, and the application of organic fertilizer. In contrast, household size, access to credit, and the distance between farmers’ residences and their plantations do not significantly affect the efficiency of smallholder oil palm farming.